Living with art - Getlein, Mark (New York, NY McGraw-Hill Education, 2020)
"Art is part of our lives, from the monuments in our communities, to the fashions we wear and the media images we take in, to the exhibits on display in museums and galleries. It permeates our daily life. But why do we study art? How do we talk about Art? Living with Art helps students see art in everyday life by fostering a greater understanding and appreciation of art. Taking a step further, Getlein equips students with the tools necessary to analyze, digest, and uphold a life-long enthusiasm for art. "--
Living with art -- What is art? -- Themes of art -- The visual elements -- Principles of design -- Drawing -- Painting -- Prints -- Camera and computer arts -- Graphic design -- Sculpture and installation -- Arts of ritual and daily life -- Architecture -- Ancient Mediterranean worlds -- Christianity and the formation of Europe -- The Renaissance -- The 17th and 18th centuries -- Arts of Islam and of Africa -- Arts of Asia : India, China, and Japan -- Arts of the Pacific and of the Americas -- The modern world : 1800-1945 -- From modern to postmodern -- Contemporary art around the world.
Includes bibliographical references and index.
Keywords: Art appreciation